ANALISIS TREND PERAMALAN EFEKTIVITAS PENDAPATAN PAJAK KENDARAAN BERMOTOR (PKB) DAN BEA BALIK NAMA KENDARAAN BERMOTOR (BBN-KB) DI DISPENDA PROVINSI BENGKULU TAHUN 2010-2014 - Susena, Karona Cahya; -, Nurzam (Universitas Dehasen Bengkulu, 2016)
Karona Cahya Susena, Nurzam: The purpose of this study to determine the effectiveness of the trend of the motor vehicle tax revenue and income transfer tax DISPENDA motor vehicle in the province of Bengkulu. This study Brazilians Descriptive Analysis with sample used in this study is data Motor vehicle tax and motor vehicle title transfer fee, and Local Revenue Data Bengkulu province in 2010-2014. Least Square method used for forecasting.Results of this study illustrate the effectiveness of the actual revenue and BBN-KB PKB. Equally terjadai in 2011 amounted to 122.26%, and 129.42%. PKB forecasting results in 2015 amounted to USD 194 525 355 399 is forecast to increase in 2017 amounted to 230 315 333 298. BBN-KB forecasting results 2015 BBN-KB revenue of Rp 192 990 945 600 is forecast to increase in 2017 amounted to 213 961 622 200.Keyword: Trend Forecasting, Motor Vehicle Tax and Transfer Tax Motor Vehicle